Arabic Language and Religious Identity Construction in Online Da’wah Media - Kamila, Fariha Zahra (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
In various digital da’wah content, the use of Arabic is an element that is almost always present, whether in the form of religious terms, quotations from the Qur’an and hadith, or certain expressions. Now, Arabic is not only a language of religious study, but also a symbol of Islamic identity that has authority and authenticity. This study aims to analyze the role of Arabic in the construction of religious identity in online da’wah media, particularly on social media platforms that are widely accessed by the public. This study uses a qualitative method with a discourse analysis approach to da’wah content in the form of text, captions, videos, and audience interactions on social media. The results show that the use of Arabic in online da’wah media appears in various forms, including opening greetings, direct quotations from the Qur’an and hadith, religious terms, code-mixing, transliteration, and the use of Arabic-style visual symbols. Functionally, Arabic serves as a marker of religious legitimacy, reinforces da’wah messages, and is a means of building the collective identity of the Muslim community in the digital space. In addition, the use of Arabic also influences the audience’s perception of the credibility of the da’wah messenger. Thus, Arabic in online da’wah media not only has a communicative function but also a symbolic and ideological function in shaping and strengthening the religious identity of the audience. This research is expected to add insight and references to the study of Arabic, sociolinguistics, and digital da’wah.